2016
DOI: 10.1590/0103-8478cr20150938
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in antioxidant metabolism in coffee leaves infected by Cercospora coffeicola

Abstract: Brown eye spot (BE) caused by Cercospora coffeicola is the main disease of coffee crop. A variation in symptoms of BE has been reported in the field, raising suspicion of occurrence of new species. However, information about coffee- C. coffeicola interaction is still limited. This research aimed to determine the difference between antioxidant metabolism of coffee plants cultivar Mundo Novo inoculated with a strain isolated from a common BE lesion (CML 2984) and a strain isolated from a black BE lesion (CML 298… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 22 publications
1
3
0
Order By: Relevance
“…This suggests a relevant role of these enzymes in the defense metabolism of the host plant. Andrade et al (2016) also have reported a similar finding in coffee (Coffea arabica L.) crops infected with C. caffeicola, where the activity of PAL, POX, and SOD was subsequently increased at 24 and 48 hai. This depicts an elevated antioxidant activity because of invasion and subsequent infection by the hemibiotrophic pathogen.…”
Section: Discussionsupporting
confidence: 66%
“…This suggests a relevant role of these enzymes in the defense metabolism of the host plant. Andrade et al (2016) also have reported a similar finding in coffee (Coffea arabica L.) crops infected with C. caffeicola, where the activity of PAL, POX, and SOD was subsequently increased at 24 and 48 hai. This depicts an elevated antioxidant activity because of invasion and subsequent infection by the hemibiotrophic pathogen.…”
Section: Discussionsupporting
confidence: 66%
“…Brown Eye Spot or Cercospora Blotch caused by Cercospora coffeicola, has been reported on coffee. Besides, Andrade et al [50] showed that isolates producing brown eye spot and black spot can also cause prompt alterations in the antioxidant metabolism of coffee leaves. Armillaria root rot caused by Armillaria sp., has been reported on coffee, and this disease leads to coffee plant rot and the eventual death of the plant.…”
Section: Pathogen Effect On Coffee and Coffee Diseasementioning
confidence: 99%
“…The methods commonly used for plant health protection in coffee crops include the use of backpack sprayers, atomizers, and hydro-pneumatic and pneumatic sprayers. The limitations of these options are scarcity of specialized workers, limited operational capacity, low application efficiency, and excessive application rates; these combined factors result in losses of product to the soil, and environmental and human contaminations [12,13].…”
Section: Introductionmentioning
confidence: 99%